2015
DOI: 10.1103/physreva.91.062320
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence in adiabatic quantum computation

Abstract: Recent experiments with increasingly larger numbers of qubits have sparked renewed interest in adiabatic quantum computation, and in particular quantum annealing. A central question that is repeatedly asked is whether quantum features of the evolution can survive over the long time-scales used for quantum annealing relative to standard measures of the decoherence time. We reconsider the role of decoherence in adiabatic quantum computation and quantum annealing using the adiabatic quantum master equation formal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
179
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(187 citation statements)
references
References 76 publications
6
179
0
2
Order By: Relevance
“…The Oðt −2 op Þ diabatic transition probability is characteristic of any continuous, but otherwise generic, time dependence. A set of more general results show that errors become smaller as the evolution becomes smoother [9][10][11]. If the first k derivatives of the Hamiltonian exist and are continuous, then the diabatic corrections to the transition probability vanish as Oðt −2k−2 op Þ.…”
Section: Quasiadiabatic Evolution Of Two-level Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Oðt −2 op Þ diabatic transition probability is characteristic of any continuous, but otherwise generic, time dependence. A set of more general results show that errors become smaller as the evolution becomes smoother [9][10][11]. If the first k derivatives of the Hamiltonian exist and are continuous, then the diabatic corrections to the transition probability vanish as Oðt −2k−2 op Þ.…”
Section: Quasiadiabatic Evolution Of Two-level Systemsmentioning
confidence: 99%
“…However, the scaling of diabatic corrections is sensitive to the precise time dependence of the parameters in the Hamiltonian. In particular, the corrections are Oð1=t kþ1 op Þ when the time dependence is C k smooth [9][10][11], and they are exponentially suppressed when the time dependence is analytic [12][13][14][15][16]. (Infinitely smooth C ∞ time dependence may result in stretched exponential decay of corrections.)…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AQC is affected by noise present in any realistic implementation. It has been suggested that AQC may be inherently robust against noise [12,13] and that the presence of an environment may even improve performance [14]. Adiabatic evolution is particularly susceptible to noise when the gap between the ground state and the excited states is small.…”
mentioning
confidence: 99%
“…In the closed system setting, starting in the ground state of H(0) and evolving adiabatically, the system is guaranteed to reach the ground state of H I with high probability [15][16][17]. Although adiabatic dynamics is robust against certain forms of decoherence appearing in the more realistic open system setting [10,[18][19][20][21][22][23], it remains susceptible to thermal noise and specification errors [24], which can jeopardize the efficiency of the quantum computation. Therefore, any scalable quantum annealing architecture will require quantum error correction [25].…”
Section: Introductionmentioning
confidence: 99%